ANALISIS PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP EARNING RESPONSE COEFICIENT DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - R Rosiyana Dewi; Mariani Sitinjak (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2009)
The purpose of this research is to know that company characteristics toward social disclosure and Earning Response Coefficient (ERC) on manufacture companies is listed in Indonesia Stock Exchange. Independent variables in this research are profitability, leverage, and company size with ethnic of company leaders as a control variable. Intervening variable in this research is social disclosure. Dependent variable is Earning Response Coefficient (ERC). Fourty-seven registered companies in Indonesia Stock Exchange were used as research sample. These samples were selected by using purposive sampling method. Analysis hypothesis is using Regression, before hypothesis test, normality data test using kolmogorov-smirnov and P-Plot test. The result concluded by using Regression there are both profitability and company size have influences to social disclosure. Corporate Social Responsibility (CSR) also have influence too to Earning Response Coefficient (ERC). In third model, only company size have influence to Earning Response Coefficient (ERC)